Efetividade das medidas de controle e prevenção das infecções em unidade neonatal de um hospital público de referência na Amazônia - Saraty, Salma Brito [UNIFESP] (2011)
Introduction: Recent researches have emphasized zero tolerance against nosocomial infection (NI), no longer accepted as a consequence of admission to the Neonatal Intensive Care Unit (NICU). Objective: To evaluate the effectiveness of the implementation of control and prevention measures on the incidence density of NI in the neonatal ICU. Method: Prospective cohort study with intervention, which included infants with one or more NNISS’s criteria, performed in a reference public neonatal ICU in the Amazon region. The evaluation was made in two periods: pre-intervention (Jan/01/05 - Jun/30/05) with 1173 patients and postintervention (Jan/01/06 - Jun/30/06) with 855 patients. The intervention included the implementation of team training on the technique for hand hygiene (Jul/05), 2% chlorhexidine for skin antisepsis in surgical dressing and vascular puncture and 70% alcohol gel for hand hygiene (Sep/05), rationalization of antimicrobial, hematological score and C-reactive protein serials for suspension of antibiotic therapy (Sep/05) and contact isolation to NI caused by resistant germs (Nov/05). During the study, the percutaneous inserted central catheter was not used. NI was considered according criteria of Garner et al (1988). Monthly incidence densities of NI and the density of central catheter and mechanical ventilation were calculated in pre-and post-intervention period. Clinical characteristics between the two groups were compared with test t and chi-square and the incidence densities of NI and the densities of catheters and ventilators, according to the Poisson distribution. Results: Demographic characteristics were similar in both periods (average birthweight 2250g and 34 weeks gestational age, BW <1500 g - 18%, male - 53% and major surgery - 4%). The period pre-intervention versus post-intervention showed patients with NI - 22% vs 13% (p <0.001) and VLBW infants with NI - 61% vs 27% (p <0.001). The number of patient-days was 16,606 and 15,060 respectively in pre and postintervention. The comparison among the two period showed that the incidence density of NI reduced from 20.6 to 10.0 per 1000 patient-days and the density of bloodstream infection associated with catheter use was 30.5 to 10.0 per 1000 catheter-days, while the density of central catheter use increased from 50.1 to 63.6. The pneumonia associated to mechanical ventilation was reduced from 22.9 to 6.5 per 1000 ventilator-days, and the density of use of ventilation remained between 11.6 and 15.5 in the two periods. Death related to NI occurred in 63% of patients before intervention and decrease to 13% after the intervention (p <0.001). Conclusion: Efforts associated with measures of prevention and infection control have resulted in significant decrease of incidences of nosocomial infection in neonatal intensive care unit of the Amazon.